Advertising in a Quantified World: A Proposed Model of Consumer Trust, Attitude Toward Personalized Advertising And Outcome Expectancies. Issue 1 (2nd January 2019) - Brinson, Nancy H.; Eastin, Matthew S.; Bright, Laura F.
Abstract: As consumers increasingly integrate quantified self (QS) health and fitness tracking devices into their lives, the data they amass not only offer to help users live healthier lives, but also present opportunities for advertisers to target them with personalized messages based on their health-related behaviors. This survey-based study, utilizing a theoretical foundation of uses and gratifications (U&G) and communication privacy management (CPM), examines perceptions about the expected outcomes of convenient information seeking, personal status, and monetary incentives, in tandem with concerns about information privacy to predict QS health and fitness tracking device use, as well as attitudes about personalized advertising based on these data. Findings from a structural equation model analysis suggest this integrated theoretical approach offers helpful insights to advertisers seeking to leverage consumer data offered by QS health and fitness devices.